Problem Solving Ability Judging from Adversity Quotient on Problem Based Learning Model Assisted by Ethnomathematics Module (Universitas Negeri Semarang, 2022)
The purpose of this study is to characterize students' problem-solving skills based on the adversity quotient in the PBL model learning supported by the ethnomathematics module. This form of research is an explanatory sequential model with mixed methods. The participants in this study were eighth graders from SMP Negeri 1 Nita during the 2020/21 academic year. The experimental class employs a problem-based learning model with an ethnomathematics module, while the control class employs a problem-based learning model alone. Before beginning the study, students in the experimental class were given a questionnaire to establish their adversity quotient category: quitter, camper, or climber. Two students were chosen for qualitative analysis of each category. Results from problem-solving aptitude tests, interviews, questionnaires, and documentation were used to collect data. The average completeness test, classical completeness test, average difference test, different percentage test, and influence test were used to analyze quantitative data. The results of the study reveal that the adversity quotient of pupils influences their problem-solving skills. The ability of research volunteers from each adversity quotient category to solve problems differs. Q1 subjects achieved two problem-solving indicators, while Q2 subjects achieved three problem-solving indicators. CA1 subjects attained three problem-solving indicators, while CA2 subjects attained four problem-solving indicators. Subjects CL1 and CL2 obtained four problem-solving indications in the climber category.